Clinical Evaluation of Vishtindukadi Vati and Mansayadi Kwatha Alongwith Abhyang in the Management of Opium (Papaver Somniferum Linn) Addiction - Ritu Kapoor; Manoj Kumar Adlakha; Chandan Singh (Journal of Ayurveda, 2025)
Introduction: Opioid use is prevalent with significant burden of disease globally. Opioid use is associated with negative effect such as risk for opioid overdose and risk of infections as well as negative impact on families and employment. The addicts become irresponsible, unsocial, and economically poor and induce physical and mental disorders. The addicts not only ruin themselves but also affect family, society, and disturb national structure adversely. Addictions lead to feelings of failure, hopelessness, guilt, and humiliation. It is the need of hour to focus on effective practices which yield good results. To tackle this problem, knowledge of different system of medicine prevailing globally is required. Ayurved has much to do in this field. The present study with Vishatindukadi Vati and Mansayadi Kwatha alongwith abhyang was conducted with the intention to analyze the effectiveness in opium withdrawals. Methods: A total of 100 subjects of opium addiction (who fulfilled the inclusion and diagnostic criteria) had been selected and were given Vishatindukadi Vati (250 mg twice a day orally with leukwarm water) and Mansayadi Kwatha (20 ml twice a day orally) along with abhyang with tila tail for 21 days. Statistical analysis of the COWS score and objective parameters was done by the appropriated test. Result: The study was found to be statistically significant in reducing the COWS score (P < 0.0001). Conclusion: The study concluded that Vishtindukadi vati and Mansayadi kwatha along with abhyang are effective in the management of opium withdrawals.